Student Learning Activities Using Realistic Mathematics Education (RME) - Mega Ratrisna; Abdul Taram (Universitas Muhammadiyah Surabaya, 2018)
The aims of this research is to increase student activity in learning mathematics by using Realistic Mathematics Education (RME) in class VIII SMP Muhammadiyah 2 Prambanan. The study was conducted two siklus. Data collection techniques used are observation, interview, documentation and triangulation. Instrument research observation sheet and interview. Instrument analysis using content validity. The analysis used is descriptive qualitative. The results showed that Realistic Mathematics Education (RME) can increase student learning activity This is evident from the observation of student activity in learning every siklus has increased, that is average of observation percentage of student activity in siklus I 50,623% (enough), and at siklus II increased to 61.960% (good). From the results of interviews with students showed a positive response on student learning activity.